Proceedings of the Seventh International Learning Analytics &Amp; Knowledge Conference 2017
DOI: 10.1145/3027385.3027443
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning self-regulated learning profiles in hypermedia-learning environments

Abstract: Self-regulated learning (SRL) is a process that highly fluctuates as students actively deploy their metacognitive and cognitive processes during learning. In this paper, we apply an extension of latent profiling, latent transition analysis (LTA), which investigates the longitudinal development of students' SRL latent class memberships over time. We will briefly review the theoretical foundations of SRL and discuss the value of using LTA to investigate this multidimensional concept. This study is based on colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…A possible explanation is that the system helps to apply the metacognitive skills of orientation, planning, evaluation, and reflection to problem-solving tasks, which helps to define the problem-solving process through graduated steps of progressive difficulty (Azevedo, 2005; Winne, 2014; Höök and Eckerdal, 2015; Cerezo et al, 2016; Harley et al, 2017). Moreover, this process facilitates SRL (Cerezo et al, 2016; Sáiz and Montero, 2016; Lau et al, 2017) and the personalized feedback of the teacher in real time, which increases the motivation of the student toward the learning material (Hattie and Timperley, 2007; Zimmerman and Moylan, 2009; Segedy and Biswas, 2015). The use of LMS that incorporate hypermedia Smart Tutoring Systems includes all these characteristics in the platform for the strengthening of object-level and meta-level structures (Cuba-Ricardo et al, 2015; Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that the system helps to apply the metacognitive skills of orientation, planning, evaluation, and reflection to problem-solving tasks, which helps to define the problem-solving process through graduated steps of progressive difficulty (Azevedo, 2005; Winne, 2014; Höök and Eckerdal, 2015; Cerezo et al, 2016; Harley et al, 2017). Moreover, this process facilitates SRL (Cerezo et al, 2016; Sáiz and Montero, 2016; Lau et al, 2017) and the personalized feedback of the teacher in real time, which increases the motivation of the student toward the learning material (Hattie and Timperley, 2007; Zimmerman and Moylan, 2009; Segedy and Biswas, 2015). The use of LMS that incorporate hypermedia Smart Tutoring Systems includes all these characteristics in the platform for the strengthening of object-level and meta-level structures (Cuba-Ricardo et al, 2015; Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned Intelligent Tutoring Systems include the use of hypermedia systems, that provide feedback on the learning process and support to the student or group of students in real time. In addition, those systems can provide different types of regulation and can predict learning results (Lau et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, blended learning (80% interaction in the LMS) is a space where feedback is done 80% of the time through F2F and 20% through LMS [18,23], hereafter referred to as Blended Learning type 2. Recent investigations have found that the replacement blended environment accompanied by the use of active methodologies (e.g., PBL, use of hypermedia resources, flipped learning experiences, and quizzes, or all at once) improved the learning results of students [3,24]. These achievements are especially significant in university environments [25,26] because future graduates will have to develop collaborative work skills, problem-solving independence, and the use of new technologies.…”
Section: Design Of the Blended-learning Space In Nursing Instructionmentioning
confidence: 99%
“…Recent investigations have confirmed that if such a methodology is accompanied by the use of hypermedia resources (e.g., flipped learning experiences, quizzes, use of wikis, on-line glossaries, etc. ), then acquisition of deep learning is strengthened in students [3]. Deep learning is a concept developed in the framework of the taxonomy of Bloom [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to corroborate claims drawn from the process data by aligning it with outcomes. This study builds on recent approaches to tackling this issue by applying student‐profiling methods such as Latent Profile Analysis (Barnard‐Brak, Lan, & Paton, 2010; Jang et al ., 2017; Lau, Sinclair, Taub, Azevedo, & Jang, 2017) to model the relationships between SRL and TPACK outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 99%